A friction performance evaluation method based on micro-texture size characteristics
Patent Information
- Application Number
- CN202610917430.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-23
AI Technical Summary
(1)试验成本高、耗时长;
1.可实现织构化氧化锆陶瓷表面摩擦性能的快速评价,为微织构设计提供参考:
Smart Images

Figure CN122961895A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microtextured surface technology, and in particular to a method for evaluating frictional performance based on the dimensional characteristics of microtexture. Background Technology
[0002] Microtextured surfaces have gained widespread attention in recent years in fields such as mechanical components, microfluidic chips, and biomedical devices due to their excellent properties in lubrication, wear resistance, and self-cleaning. Traditional methods for evaluating frictional performance mainly rely on tribological tests in the laboratory under different loading, lubrication conditions, and contact geometries, evaluating surface properties by measuring indicators such as the coefficient of friction, wear rate, and changes in surface morphology. While these methods can directly reflect frictional behavior under actual working conditions, they have the following main shortcomings: (1) The experiment is costly and time-consuming; To obtain statistically significant friction performance data, it is usually necessary to conduct a large number of repeated tests under various loads, speeds, temperatures and lubricating media conditions. Furthermore, the test equipment, sample preparation and surface morphology characterization also require a lot of manpower, material resources and time.
[0003] (2) Lack of generalizable quantitative physical models; Existing research largely focuses on empirical correlations of macroscopic friction coefficients or local contact analyses based on finite element and molecular dynamics simulations. This makes it difficult to establish a direct and quantifiable physical model linking microscopic surface structures (such as the size, shape, and distribution of microtexture units) to macroscopic frictional properties. Consequently, designing novel microtextured surfaces still requires optimizing structural features through experimental analysis, which is inefficient.
[0004] After searching the literature, Toward the mechanisms of surface texturing on the wearbehavior of dental zirconia ceramics under dry and saliva lubricatedconditions, Wear In this paper, vol. 484-485, 2021, p. 203845, ISSN 0043-1648, the changes in the coefficient of friction were recorded by rubbing textured 3Y-TZP ceramic material surfaces against friction pairs made of Si3N4 and 304 steel, respectively. However, the coefficient of friction of some textured surfaces during the rubbing process with the friction pairs was greater than or close to that of unprocessed surfaces with microtextures. These microtextures are not considered in practical applications.
[0005] Therefore, it is of great significance to study a friction performance evaluation method based on microtexture size characteristics to solve the problems of high test costs, long test time and lack of generalizable quantitative physical models. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the existing technology and provide a method for evaluating friction performance based on microtexture size characteristics.
[0007] The objective of this invention can be achieved through the following technical solutions: A method for evaluating frictional performance based on microtexture size characteristics, comprising: Step S1: Using laser sintering technology, a microtexture is formed on one surface of the 3Y-TZP ceramic material to obtain a textured 3Y-TZP ceramic material; Step S2: Fix the textured 3Y-TZP ceramic material and the standard grinding pair in the lower and upper clamps of the friction testing machine, respectively, to form an upper and lower friction pair for friction testing; Step S3: During the friction test, friction performance evaluation indicators are used. The tribological properties of the textured 3Y-TZP ceramic material surface were evaluated.
[0008] As a preferred technical solution, the friction performance evaluation index The calculation formula is as follows: in, , , and The coefficient is constant. This represents the area ratio of microtextured units in the microtextured region on the textured surface. To describe the critical roll angle and Sub-model of the relationship between them This represents the average of the shortest distances from all locations within the microtextured region to the gaps between textured units. This represents the critical roll angle of the surface of 3Y-TZP ceramic material without microtexturation. This represents the average of the shortest distances from all locations on the surface of the unprocessed 3Y-TZP ceramic material to the edge. To describe the adhesion between the upper and lower friction pairs and Sub-models of the relationships between them.
[0009] As a preferred technical solution, the critical roll angle The calculation formula is as follows: in For droplet propulsion angle, For droplet recoil angle, For liquid-gas interfacial tension, For droplet mass, For gravitational acceleration, This represents the projected width of the contact line.
[0010] As a preferred technical solution, the projection width of the contact line Expressed as Functions: The droplet propulsion angle Expressed as Functions: The droplet recoil angle Expressed as Functions: in Let be the radius of the sphere corresponding to the droplet cap. To achieve the static equilibrium contact angle of the textured surface, The droplet propulsion angle on the surface of unprocessed 3Y-TZP ceramic material with microtexturation. The receding angle of droplets on the surface of unprocessed 3Y-TZP ceramic material with microtexturation; The droplet back angle Expressed as The function of the droplet propulsion angle Expressed as The function, the projection width of the contact line Expressed as Substitute the function into the critical roll angle From the calculation formula, we get The functional relationship.
[0011] As a preferred technical solution, the The functional relationship is as follows: In the formula, and C It is a constant. , , The contact angle of the surface of 3Y-TZP ceramic material without microtexturation is shown. For the mass of the droplet, It is the acceleration due to gravity. For liquid-gas interfacial tension, The droplet propulsion angle on the surface of unprocessed 3Y-TZP ceramic material with microtexturation. The receding angle of droplets on the surface of 3Y-TZP ceramic material without microtexturation.
[0012] As a preferred technical solution, the The functional relationship is obtained by integrating the interaction forces between the atoms constituting the upper friction pair and the atoms constituting the lower friction pair based on the Lennard-Jones potential energy theory.
[0013] 7. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 2, characterized in that, the... The functional relationship is as follows: in, and These are the atomic densities of the upper and lower friction pairs, respectively. and These represent the contact areas of the upper and lower friction pairs, respectively. a and b It is a constant. It is the root mean square of the height distribution of all micro-convexities. This indicates the distance between the atoms that make up the upper and lower friction pairs.
[0014] As a preferred technical solution, the average value of the shortest distance from all locations in the microtextured region to the gaps between texture units is... The calculation formula is as follows: in, For the area of the microtexture unit, Points on microtexture units The closest distance to the gap between texture units.
[0015] As a preferred technical solution, step S3 specifically includes: Step S301, using the surface of the unprocessed 3Y-TZP ceramic material to form a microtexture. When the coefficient of friction is 0 To establish standards M The linear relationship between the coefficient of friction; Step S302, obtain the microtexture size parameters and Its friction performance evaluation index The calculation formula yields the friction performance evaluation index. M This leads to the friction coefficient, which is used to evaluate the frictional properties of the textured 3Y-TZP ceramic material surface.
[0016] As a preferred technical solution, the M The linear relationship between the coefficient of friction and the coefficient of friction is: The coefficient of friction from μ The process of decreasing from 0 to 0 corresponds linearly to the friction performance evaluation index. M The formula for increasing from 0 to 100 is as follows: in μ 0 represents the friction coefficient of the surface of the unprocessed 3Y-TZP ceramic material with microtexture, and its value ranges from 0.40 to 0.50. μ denoted as the friction coefficient of the textured surface.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. It enables rapid evaluation of the tribological properties of textured zirconia ceramic surfaces, providing a reference for microtexture design: Traditional evaluation methods require numerous repeated tests under various load, speed, and lubrication conditions, and sample preparation and morphology characterization are time-consuming. This method only requires inputting the dimensional parameters of the microtexture, and can directly calculate the friction performance evaluation index M through a pre-trained quantitative physical model, without waiting for long-term friction tests, thus significantly shortening the evaluation time.
[0018] 2. The constructed physical model of frictional properties has strong versatility and can significantly reduce the cost of experimental verification. Traditional research often relies on empirical correlations or local simulations, which cannot establish a direct quantitative relationship between micro-texture characteristics and macro-friction properties. New structural designs require repeated trial and error experiments. This model couples three core physical mechanisms. 1) Based on the droplet rolling characteristics Sub-model to quantify the relationship between the area ratio of microtexture and surface lubrication / self-cleaning ability; 2) Based on the logic of wear debris transport A computational model quantifies the relationship between texture size and wear debris storage and isolation capabilities; 3) Based on Lennard-Jones potential energy theory The sub-model quantifies the relationship between area ratio and interfacial adhesion.
[0019] The model formed by the integration of the three mechanisms can be directly evaluated and optimized in the design phase without the need for extensive physical testing.
[0020] 3. It can significantly improve the development efficiency of novel microtextured surfaces. The model has been experimentally verified through multiple sets of biomimetic textures (imitating lotus leaves, fish scales, clams, feathers, microgrooves, etc.), and the deviation between the predicted friction coefficient and the actual experimental value is only 6.5%~7.6%, which meets the design guidance requirements. Researchers can quickly screen invalid texture schemes (such as designs with friction coefficients close to or even higher than those of untextured surfaces) without physical samples, greatly reducing redundant experiments and shortening the development cycle. Attached Figure Description
[0021] Figure 1 Scanning electron microscope (SEM) images of the unprocessed surface with microtextured features and three biomimetic microtextured surfaces; among them, Figure 1 (a) is the unprocessed surface with microtextured structure (original surface); Figure 1 (b) is a lotus leaf-shaped microtextured surface; Figure 1 (c) is a surface with a fish-scale-like microtexture; Figure 1 (d) is a clam-like microtextured surface; Figure 2 The graph shows the changes in the friction coefficient of the unprocessed surface and the three types of microtextured surfaces during actual friction and wear experiments. Figure 3 These are scanning electron microscope (SEM) images of two biomimetic microtextures used for model validation; among them, Figure 3 (a) is a feather-like microtextured surface; Figure 3 (b) is a microgroove textured surface; Figure 4 The graph shows the change in friction coefficient during the friction and wear experiment for two types of biomimetic microtextures used for model validation and the unprocessed microtexture. Figure 5 This is a flowchart illustrating the specific process of the method of the present invention. Detailed Implementation
[0022] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0023] Example 1: like Figure 5 As shown, a method for evaluating friction performance based on microtexture size characteristics is described below: Step S1: Using laser sintering technology, a microtexture is formed on one surface of the 3Y-TZP ceramic material to obtain a textured 3Y-TZP ceramic material; Step S2: The textured 3Y-TZP ceramic material and the standard grinding pair are fixed in the lower and upper clamps of the friction testing machine, respectively, as upper and lower friction pairs, and a friction test is performed. Step S3: During the friction test, friction performance evaluation indicators are used. The tribological properties of the textured 3Y-TZP ceramic material surface were evaluated. The The calculation formula is as follows: (1); In the formula, , , and The constant coefficient, =0.219, =1.906, =0.18, =1.229; To determine the area ratio of microtextured units in the microtextured region on the textured surface, it can be determined according to... Seek; like Figure 1 The image shows scanning electron microscope (SEM) images of the unprocessed surface with microtexture and three biomimetic microtexture surfaces. The circular, fan-shaped, and wavy positions are microtexture units, and the intervals between microtexture units are the gaps between the microtexture units. The critical roll angle and Sub-model of the relationship between them This represents the average of the shortest distances from all locations within the microtextured region to the gaps between textured units. This represents the critical roll angle of the surface of 3Y-TZP ceramic material without microtexturation. This represents the average of the shortest distances from all locations on the surface of the unprocessed 3Y-TZP ceramic material to the edge. To describe the adhesion between the upper and lower friction pairs and Sub-models of the relationships between them; in, The functional relationship is as follows: (2); The establishment process is as follows: First, based on the droplet propulsion angle Droplet recoil angle Liquid-gas interfacial tension droplet mass Gravitational acceleration and the projection width of the contact line The relationship between the two is used to determine the critical rolling angle of the droplet on the textured surface using equation (3). : (3); Then, project the width of the contact line. Droplet propulsion angle and droplet recoil angle Expressed as Functions: (4); (5); (6); In the formula, Let be the radius of the sphere corresponding to the droplet cap. To achieve the static equilibrium contact angle of the textured surface, The droplet propulsion angle on the surface of unprocessed 3Y-TZP ceramic material with microtexturation. The receding angle of droplets on the surface of unprocessed 3Y-TZP ceramic material with microtexturation; V The volume of the droplet; Finally, substituting equations (4) to (6) into equation (3) yields the result shown in equation (2). The functional relationship; In the formula, and C It is a constant. , The equation of formula (2) is correct for both sides. By taking the derivative and analyzing, we can see that for 3Y-TZP ceramic materials, the static equilibrium contact angle of the textured surface is 71.6°, i.e. =1.316, at this time exist ∈(0, 1) As the value increases, C increases. To reduce the critical rolling angle to 0 ~ 90°, C = 1.08 can be used. The contact angle of the surface of 3Y-TZP ceramic material without microtexturation is shown. For the mass of the droplet, It is the acceleration due to gravity. The liquid-gas interfacial tension; The functional relationship is as follows: (7); The derivation of the functional relationship is as follows: Based on the Lennard-Jones potential energy theory, the interaction force between the atoms constituting the upper friction pair and the atoms constituting the lower friction pair is obtained by integrating: (8); The distance between the upper and lower friction pairsh replace According to the GW model and Hertz theory, the normal force per unit area F N The relationship between the distance between the upper and lower friction pairs can be expressed as: (9); in, N 0 This represents the total number of micro-protrusions. h Let Φ(z) be the distance between the upper and lower friction pairs, and let Φ(z) represent the height distribution of the microscopic particles on the material surface, assuming a root mean square value. The standard normal distribution E According to the formula Confirmed, among which E 1 and E 2 These are the elastic moduli of the upper and lower friction pairs, respectively. and These are the Poisson's ratios of the upper and lower friction pairs, respectively. z The height of a single microscopic particle. During the friction and wear experiment, the normal force applied between the upper and lower friction pairs is a constant. Assuming the total area of the microtextured regions is S The normal force provided by the micro-protrusions in the contact area of the microtextured surface is then... S × × = From this, the distance between the upper and lower friction pairs can be derived. h Relationship between and the area ratio of microtexture regions By analyzing implicit functions It can be known ,in, t = z - h, Used to adjust the upper and lower limits of integration from h →∞ is changed to 0→∞; to make Scaling to 0~1 is acceptable. a =0.1278, b =1, will Substituting the approximate relation into The adhesive force can be obtained from the formula as shown in formula (8). and the proportion of microtexture area The relationship between them; and These are the atomic densities of the upper and lower friction pairs, respectively. and These represent the contact areas of the upper and lower friction pairs, respectively. a and b It is a constant. It is the root mean square of the height distribution of all micro-convexities. This indicates the distance between the atoms that make up the upper and lower friction pairs.
[0024] The , , and The solution process is as follows: (1) such as Figure 1 As shown, the area percentages of the unprocessed surface with microtexture and the three types of microtextured surfaces were calculated to be 100%, 28.27%, 30.54%, and 49.56%, respectively. (2) Substituting the area proportions into equation (3), the critical rolling angles are 90°, 8.91°, 9.97°, and 20.41°, respectively. (3) The shortest distance for the unprocessed microtextured surface is calculated based on a 3mm square of friction and wear travel. By calculating the average of the shortest distances from each position to the edge, the shortest distance for the unprocessed microtextured surface can be obtained. For the three microtextured surfaces with a diameter of 500 μm, the shortest distance can be obtained by calculating the average of the shortest distances from each location to the gaps between textured units. The corresponding sizes are 35 μm, 23.07 μm, and 27.12 μm, respectively. (4) Without considering the unknown parameters, the adhesive forces of the four surfaces are integrated to obtain the adhesive forces of the four surfaces as 156.8, 16.2, 18.7 and 46.7 respectively. (5) such as Figure 2 As shown, the surface tribological performance evaluation index is based on the unprocessed surface with microtextured structure. When the coefficient of friction is 0 Using the average friction coefficient during the experiment as the standard, the corresponding evaluation index is calculated. The evaluation index values for the four surfaces were obtained as 0, 20.8, 27.7, and 14.2, respectively. (6) The critical roll angle and average shortest distance for the unprocessed microtextured surface are respectively... and Substituting the data from the four types of surfaces mentioned above into the friction performance evaluation model, we can obtain the four coefficients in the model as follows: , , and Friction performance evaluation index The calculation formula is: .
[0025] When evaluating the tribological properties of textured 3Y-TZP ceramic materials, the surface of unprocessed 3Y-TZP ceramic materials with microtextured structures is first considered. When the coefficient of friction is 0 To establish standards M The linear relationship between the coefficient of friction and the microtexture size parameters is then obtained. and Substituting it into equation (1) yields the friction performance evaluation index. M The friction coefficient is then obtained, which is used to evaluate the friction properties of the textured 3Y-TZP ceramic material surface. From the coefficient of friction μ The process of decreasing from 0 to 0 corresponds linearly to the friction performance evaluation index. M The formula for increasing from 0 to 100 is as follows: (10); in μ 0 represents the friction coefficient of the surface of the unprocessed 3Y-TZP ceramic material with microtexture, and its value ranges from 0.40 to 0.50. μ The coefficient of friction of the textured surface; The calculation formula is as follows: (11); In the formula, For the area of the microtexture unit, Points on microtexture units The closest distance to the gap between texture units.
[0026] Example 2: To verify the agreement between the physical model of the microtextured surface friction performance constructed in this invention and experimental data, a specific embodiment of the friction performance evaluation method based on microtexture size characteristics of this invention is described below: 1. Experimental materials and equipment; Ceramic samples: 3Y-TZP ceramics, prepared using micro-nano processing (i.e., laser sintering technology) to achieve various solid-liquid contact area ratios. The microtextured surface, that is, multiple pieces of the same size Figure 1 The materials shown in (a) are processed into Figure 1 (b) Figure 1 (c) and Figure 1 The surface shown in (d).
[0027] Friction pair: Natural human molars, selected from patients aged 20-30, extracted 2-3 days before the experiment (teeth will also wear down during the friction and wear experiment, so multiple natural teeth from different patients are used in the experiment), with similar geometric shapes to ensure consistency; fixed to the custom workpiece using AB glue.
[0028] Friction testing machine: Bruker UMT TriboLab multi-functional friction and wear testing machine, with an upper clamp to fix natural teeth and a lower clamp to fix 3Y-TZP ceramic samples.
[0029] 2. Experimental parameter design; Referencing physiological parameters of the human chewing process: Duration of a single contact: 0.1 s; Relative sliding distance: 0.9~1.2 mm; Typical chewing force: 4 N; Therefore, the friction and wear test is set as follows: Reciprocating stroke: 3 mm; Reciprocating frequency: 2 Hz (corresponding to a sliding linear velocity of approximately 12 mm / s); Normal load: 4 N; Number of loops: 2000; Lubrication conditions: Artificial saliva is dropped into the friction contact area to simulate the oral cavity environment.
[0030] 3. Measurement and characterization; Friction force recording: During the test, the testing machine collects the horizontal friction force in real time. F t The coefficient of friction was correlated with the number of cycles to obtain a curve showing the change of friction coefficient with time / number of cycles.
[0031] The specific steps of the friction performance evaluation method based on microtexture size characteristics are as follows: (1) such as Figure 3 As shown, the area proportions of the two microtextures used for model validation and the average of the shortest distances from each location to the edge are calculated respectively, thus obtaining the area proportions of the two microtextures. The percentages were 32.82% and 30.55% respectively, the shortest distance. The thicknesses are 13.25 μm and 20.97 μm, respectively. (2) The proportion of microtexture area Substituting these values into equations (2) and (7) respectively, we obtain the critical rolling angles for the two microtextures as 11.05° and 9.95°, respectively, and the adhesion... They are 21.5 and 18.8 respectively; (3) Substituting the above data into the evaluation model, we can obtain the friction performance evaluation indexes for the two microtextures. M The values are 33.9 and 29.5 respectively, corresponding to friction coefficients of 0.33 and 0.31. (4) such as Figure 4 As shown, the average friction coefficients of the two microtextures used for model validation during the experiment were 0.355 and 0.290, respectively, with deviations from the theoretical friction coefficients validated by the model of 7.6% and 6.5%. Considering that the model cannot fully account for all influencing factors and that there are uncertainties in the experiment, the model can be used to guide the design of microtextures.
[0032] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A method for evaluating frictional performance based on microtexture dimensional characteristics, characterized in that, include: Step S1: Using laser sintering technology, a microtexture is formed on one surface of the 3Y-TZP ceramic material to obtain a textured 3Y-TZP ceramic material; Step S2: Fix the textured 3Y-TZP ceramic material and the standard grinding pair in the lower and upper clamps of the friction testing machine, respectively, to form an upper and lower friction pair for friction testing; Step S3: During the friction test, friction performance evaluation indicators are used. The tribological properties of the textured 3Y-TZP ceramic material surface were evaluated.
2. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 1, characterized in that, The friction performance evaluation index The calculation formula is as follows: in, , , and The coefficient is constant. This represents the area ratio of microtextured units in the microtextured region on the textured surface. To describe the critical roll angle and Sub-model of the relationship between them This represents the average of the shortest distances from all locations within the microtextured region to the gaps between textured units. This represents the critical roll angle of the surface of 3Y-TZP ceramic material without microtexturation. This represents the average of the shortest distances from all locations on the surface of the unprocessed 3Y-TZP ceramic material to the edge. To describe the adhesion between the upper and lower friction pairs and Sub-models of the relationships between them.
3. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 2, characterized in that, The critical roll angle The calculation formula is as follows: in For droplet propulsion angle, For droplet recoil angle, For liquid-gas interfacial tension, For droplet mass, For gravitational acceleration, This represents the projected width of the contact line.
4. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 3, characterized in that, The projection width of the contact line Expressed as Functions: The droplet propulsion angle Expressed as Functions: The droplet recoil angle Expressed as Functions: in Let be the radius of the sphere corresponding to the droplet cap. To achieve the static equilibrium contact angle of the textured surface, The droplet propulsion angle on the surface of unprocessed 3Y-TZP ceramic material with microtexturation. The receding angle of droplets on the surface of unprocessed 3Y-TZP ceramic material with microtexturation; The droplet back angle Expressed as The function of the droplet propulsion angle Expressed as The function, the projection width of the contact line Expressed as Substitute the function into the critical roll angle From the calculation formula, we get The functional relationship.
5. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 4, characterized in that, The The functional relationship is as follows: In the formula, and C It is a constant. , , The contact angle of the surface of 3Y-TZP ceramic material without microtexturation is shown. For the mass of the droplet, It is the acceleration due to gravity. For liquid-gas interfacial tension, The droplet propulsion angle on the surface of unprocessed 3Y-TZP ceramic material with microtexturation. The receding angle of droplets on the surface of 3Y-TZP ceramic material without microtexture formation.
6. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 2, characterized in that, The The functional relationship is obtained by integrating the interaction forces between the atoms constituting the upper friction pair and the atoms constituting the lower friction pair based on the Lennard-Jones potential energy theory.
7. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 2, characterized in that, The The functional relationship is as follows: in, and These are the atomic densities of the upper and lower friction pairs, respectively. and These represent the contact areas of the upper and lower friction pairs, respectively. a and b It is a constant. It is the root mean square of the height distribution of all micro-convexities. This indicates the distance between the atoms that make up the upper and lower friction pairs.
8. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 1, characterized in that, The average value of the shortest distance from all locations in the microtextured region to the gaps between texture units. The calculation formula is as follows: in, For the area of the microtexture unit, Points on microtexture units The closest distance to the gap between texture units.
9. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 1, characterized in that, Step S3 specifically includes: Step S301, using the surface of the unprocessed 3Y-TZP ceramic material to form a microtexture. When the coefficient of friction is 0 To establish standards M The linear relationship between the coefficient of friction; Step S302, obtain the microtexture size parameters and Its friction performance evaluation index The calculation formula yields the friction performance evaluation index. M This leads to the friction coefficient, which is used to evaluate the frictional properties of the textured 3Y-TZP ceramic material surface.
10. The method for evaluating frictional performance based on microtexture dimensional characteristics according to claim 9, characterized in that, The M The linear relationship between the coefficient of friction and the coefficient of friction is: The coefficient of friction from μ The process of decreasing from 0 to 0 corresponds linearly to the friction performance evaluation index. M The formula for increasing from 0 to 100 is as follows: in μ 0 represents the friction coefficient of the surface of the unprocessed 3Y-TZP ceramic material with microtexture, and its value ranges from 0.40 to 0.
50. μ denoted as the friction coefficient of the textured surface.